2021
DOI: 10.1039/c9fd00117d
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell graphene oxide–polymer hollow fibers as water filters with enhanced performance and selectivity

Abstract: Extraction of proteins from blood biological fluids requires the removal of large aggregates or cells by membrane filtration. However, conventional filters, based on simple size exclusion, do not allow to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Electrospinning, introduced and developed in the 1980s [ 1 ], remains the subject of attention for researchers as a versatile technology for producing fibers with a diverse range of diameters, morphologies, and functions. Electrospun fiber mats have found application as filters [ 2 ], membranes, substrates for tissue engineering and growth [ 3 , 4 , 5 , 6 ], wound dressings [ 7 , 8 , 9 ], and photocatalysts for water defluoridation and cleansing [ 10 , 11 ]. The properties of the fibers depend on various polymer frameworks, which differ in their biocompatibility, biodegradability, hydrophobicity, and water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning, introduced and developed in the 1980s [ 1 ], remains the subject of attention for researchers as a versatile technology for producing fibers with a diverse range of diameters, morphologies, and functions. Electrospun fiber mats have found application as filters [ 2 ], membranes, substrates for tissue engineering and growth [ 3 , 4 , 5 , 6 ], wound dressings [ 7 , 8 , 9 ], and photocatalysts for water defluoridation and cleansing [ 10 , 11 ]. The properties of the fibers depend on various polymer frameworks, which differ in their biocompatibility, biodegradability, hydrophobicity, and water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…6c). 79 The results indicated that the inner-coated PES/GO composite HFs (PES wrapped GO) had the best removal efficiency (50%) towards ciprofloxacin, followed by 20% clearance rate for the outer-coated case (GO wrapped PES). In contrast, the uncoated PES HF filters delivered insignificant filtering effects for the standard contaminants.…”
Section: Pes Compositesmentioning
confidence: 96%
“…Finally, considering a 3.5% of GO in PSU-GO HFs, the calculated release of GO after 30 min of sonication, was always lower than 0.2% (ESI, Table S8). To the best of our knowledge, this is the first case of study on release from PSU-graphene composite with a limit of quantification below the mg/L limit, typically achieved by UV-vis or TOC analyses [61].…”
Section: Water Potability and Go Release Test By Surface-enhanced Ram...mentioning
confidence: 99%